Tracking lithospheric delamination and surface processes across the Messinian salinity crisis - Frédéric Mouthereau; Louise Boschetti; Marine Larrey; Stéphanie Brichau; Nicolas E. Beaudoin; Damien Huyghe; Nick M. W. Roberts; Mathieu Daëron (Nature Communications)
Abstract Lithospheric delamination involves short-lived crustal and surface responses, alkaline magmatism, high heat flow and extension. In the Western Mediterranean, delamination is hypothesized to have triggered uplift at the origin of the Messinian Salinity Crisis (MSC). But delamination as the primary cause of uplift is questioned due to the insufficient temporal resolution. We report new U-Pb ages and clumped isotope analyses from calcite veins formed in an eastern Betic intramontane basin. They reveal a brief fluid event from 8.5 to 5 Ma linked to extension and retreating delamination. After extension, shortening and uplift began at 4.5–3 Ma across the boundary between the Cabo de Gata arc basement and the Iberia margin. We show that the MSC occurred before shortening and during delamination. Slab detachment caused the demise of the MSC, the formation of a new plate boundary fault and tectonic escape between Africa and Iberia around 5 Ma.